Formative Assessment in the Merdeka Curriculum English Textbook entitled English for Nusantara - Jajang Nooralam; Zulfa Sakhiyya (Universitas Negeri Semarang, 2022)
Using formative assessment to analyze tasks in the textbook is uncommonly used. Textbooks as the primary resources should follow the latest curriculum version in teaching-learning processes. This study aimed at investigating the implementation of formative assessment on speaking and writing activities in the